”Han kun int spela sôm I sang.” - Kristin Jonzon (Musikk og Tradisjon)
“He could not play the way I sang” is what Dansar Edvard Jonsson (1893-1976), Malung, Sweden, told the fieldworker Gertrud Sundvik when he performed together with a fiddler. The quote encapsulates a traditional singer’s take on the Scandinavian tradition of trying to demonstrate that the intonation patterns in what we today call traditional singing are hardly arbitrary. The purpose of this article is to illustrate the utility and implications of the Multi-modal Model, with a specific focus on melodic movements and pitch categories which “swap places”. This will be done through an analysis of the intonation in three recordings each of two songs with Dansar Edvard. The model is innovative in three ways; it implies a descriptive approach that does not presuppose any stipulated intonation pattern, the attention to intonation as something which emerges throughout a performance, and a focus on the phrase instead of the tones. The contribution is thus built on a thought structure which radically differs from those relying on abstract a priori tonal structures. This forms an attempt to look beyond norms derived from mathematical perfection.